Generating Recommendations in GDM with an Allocation of Information Granularity - Cabrerizo, Francisco Javier; Morente-Molinera, Juan Antonio; Pérez, Ignacio Javier; Urena, Raquel; Herrera-Viedma, Enrique (Aggregation Functions in Theory and in Practice, 2018)
A Group decision making process is carried out when human beings jointly make an election from a possible collection of alternatives. Here, a question of importance is to avoid winners and losers, in the sense that the choice is not any more attributable to any single individual, but all group members contribute to the decision. For this reason, the agreement or consensus achieved among all the individuals should be as high as possible. In this contribution, a feedback mechanism is presented in order to increase the consensus achieved among the decision makers involved in this kind of problems. It is based on granular computing, which is utilized here to provide the necessary flexibility to increase the consensus. The feedback mechanism is able to deal with heterogeneous contexts, that is, contexts in which the decision makers have importance degrees considering their capacity or talent to handle the problem.
Conferencia de "9th International Summer School on Aggregation Operators, AGOP 2017; Skovde; Sweden; 19 June 2017 through 22 June 2017"
Keywords: group decision making; consensus; feedback mechanism; granular computing; heterogeneous contexts; WOS(2); Scopus(2)